Deposition of W and W-RE alloys by gas-phase and plasma chemical methods - Glushko, P.I.; Yevsiukov, A.I.; Ghuravlyov, А.Yu.; Hovanskiy, N.А.; Khizhnyak, D.A.; Shirokov, B.M.; Shijan, А.V. (Вопросы атомной науки и техники, 2016)
A thermodynamic analysis of the temperature dependence of the isobaric-isothermal potential processes of rhenium, tungsten and their compositions from a mixture of a metal fluorides with molecular and atomic hydrogen is provided. The dependence of the deposition rate of tungsten and tungsten-rhenium alloys executed by plasma chemical and gas-phase methods on the substrate temperature, to power fed into discharge and the ratio of initial reagents is studied. Проведено термодинамічний аналіз температурної залежності ізобарно-ізотермічного потенціалу процесів отримання ренію, вольфраму і сплавів на їх основі з суміші фторидів металів з молекулярним і атомарним воднем. Досліджено залежність швидкості осадження вольфраму і вольфрам-ренієвих сплавів газофазним і плазмохімічним методами від температури підкладки, що вкладена в розряд потужності, і співвідношення вихідних реагентів. Проведено дослідження швидкості осадження W і W-Re-сплавів, що отримані газофазним і плазмохімічним методами, залежно від співвідношення H₂:MeF₆. Проведен термодинамический анализ температурной зависимости изобарно-изотермического потенциала процессов получения рения, вольфрама и сплавов на их основе из смеси фторидов металлов с молекулярным и атомарным водородом. Исследованы зависимости скорости осаждения вольфрама и вольфрам-рениевых сплавов газофазным и плазмохимическим методами от температуры подложки, вкладываемой в разряд мощности, и соотношения исходных реагентов. Проведено исследование скорости осаждения W и W-Re-сплавов, полученных газофазным и плазмохимическим методами, в зависимости от соотношения H₂:MeF₆.